Products 2 : 50 real-life projects uncovered. - Haller, Lynn, ....-; Dangel Cullen, Cheryl, ....- (Gloucester : Rockport, 2004)
Fifty design projects are shown in detail from concept to completion and all the stages in between for a behind-the-scenes look that uncovers the design process that produced the award winning end results. These products are the winners of the Industrial Designers Society of America's acclaimed Industrial Design Excellence Award (IDEA). Each project provides text describing the designer's insights and inspirations as well as the evolution of the illustrated project. Working drawings, sketches, process books, computer visuals, storyboards and colour photographs show the story behind the design. In these pages, you'll find cutting-edge product design ranging from electronic gadgets for the kitchen to high-tech equipment. It's the perfect book for the working product designer and the student of product design. Take a trip inside the design studios of the world's most talented product designers for a quick apprenticeship in a major commercial area of design.
Keywords: Industrieel ontwerpen